O carste sob os olhares da superfície: fragilidade, antropismo e planejamentos urbano eambiental na região cárstica de Lagoa Santa - MG - Manuela Correa Pereira (2018)
Karst landscapes, because of its natural characteristics, are more vulnerable to anthropogenic activities when compared to other landscapes whose geological substrate is composed of non carbonate rocks. In this context, it is expected that public policies of territorial and environmental character set regulations that minimize the impacts of human activities on surface. However, it hás been hypothesized that the multiplicity and the disarticulation of planning tools is an obstacle to the management in karst areas and for the protection of this landscape. To test that hypothesis, it was chosen as a research area the Lagoa Santa karst region, which since the 1980s faces the intensification of human activities, as well as the increase of environmental regulations. Therefore, this thesis aims to understand how the environmental and urban planning are used to control and regulate human activities and how managers deal with such instruments. Then, the following methodological procedures were adopted: (i) Bibliographic Research - themes: vulnerability of karst systems and environmental and urban planning; (ii) Documental Research - related to topics: Brazils an Lagoa Santa karst regions urban, hydric resources and environmental planning; (iii) Characterization of Anthropogenic Pressures - mapping and characterization of spatiotemporal evolution of human pressures in the investigated area; (iv) Focal Group - analysis of interviews with professionals Who deal with study areas territorial and environmental managements; and (v) Final Analysis - by the results of previous approaches, it was proposed to establish a dialogue between the four dimensions of this research: human pressures, fragility of karst systems, instruments for territorial andenvironmental management designed to control anthropic pressures in karst areas, and how managers deal with such instruments. From the results, it was verified that the instruments multiplicity of instruments is an obstacle to the various management scales of the study area. However, the reason of the disarticulation between these instruments is the negligence of the most conservationist instruments guidelines. It can be concluded that it is moving towards an integration of the planning instruments, which can optimize study areas territorial management. However, possibly aspects of karst protection will be suppressed, allowing serious environmental problems in the karst landscape.